2017
DOI: 10.1177/1103308817715163
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Adolescents’ Academic Achievement

Abstract: Recent empirical literature has highlighted that adolescents show gender differences in academic performance. The present study intends to disentangle the contribution of some less well-known factors to that gender difference in the fourth year of secondary education. To this aim, we use recent methodological advances in decomposition techniques. We observe that girls are less likely to get low scores than boys. More interestingly, gender differences in the returns to expectations about the future have been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 21 publications
4
25
0
4
Order By: Relevance
“…Different studies have shown that there are gender disparities in academic achievement in different countries. In more civilized and industrialized countries females have more academic achievement than males [43][44][45][46]. But in developing countries like Ethiopia, females have less access and less academic achievement than males [47].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that there are gender disparities in academic achievement in different countries. In more civilized and industrialized countries females have more academic achievement than males [43][44][45][46]. But in developing countries like Ethiopia, females have less access and less academic achievement than males [47].…”
Section: Discussionmentioning
confidence: 99%
“…Biological sex. Biological sex 43 was assessed by asking respondents: ''Are you a boy or girl?'' Male (coded 0) and female (coded 1) were represented as a dichotomous covariate.…”
Section: Covariatesmentioning
confidence: 99%
“…al., 2015). A study on gender differences in adolescents' academic achievement also observed that girls are less likely to get low scores than boys (Marcenaro-Gutierrez, et. al., 2018).…”
Section: Discussionmentioning
confidence: 97%